1254 թ. կնքված հայ-մոնղոլական պայմանագրի գնահատության շուրջ - Հովհաննիսյան Արամ (YSU Journal of International Affairs, 2014)
The estimation of Armenian-Mongol Contract in 1254 is one of the main problems of the history of Armenia. We have represented in the work how the Mongols conquered many countries and came to the borders of Kilikia. We have mentioned about the travelling of king Hetum and his negotiations with khan Mangu. We have thoroughly presented the sources of information about the contract in 1254. At the end of the work we have presented the estimations of different scientists concerning the problem mentioned above. Fot that we have combined the views of various investigators mentioning our point of view as well.